1988
DOI: 10.1093/brain/111.3.577
|View full text |Cite
|
Sign up to set email alerts
|

The Lambert-Eaton Myasthenic Syndrome

Abstract: The clinical and electrophysiological features of 50 consecutive patients with the Lambert-Eaton myasthenic syndrome (LEMS) have been analysed. Carcinoma was detected (CD group) in 25, of whom 21 had small cell lung cancer (SCLC). SCLC was evident within 2 yrs of onset of LEMS symptoms in 20/21 cases, and at 3.8 yrs in 1/21. In the cases in whom no carcinoma was detected (NCD group), 14/25 had a history of LEMS greater than 5 yrs. The dominant neurological features were similar in the CD and NCD groups, and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
428
2
19

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 652 publications
(456 citation statements)
references
References 0 publications
7
428
2
19
Order By: Relevance
“…An HLA association with HLA B8DR3 suggests an underlying genetic predisposition to autoimmunity [65] and these patients often have other autoimmune disorders, such as thyroid disease or diabetes. [64] These observations led to the first experimental studies implicating the immune system. It was shown that patients with LEMS responded clinically to plasma exchange, and daily injection of LEMS IgG antibodies into mice reproduced the principal neurophysiologic changes of LEMS.…”
Section: Immunological Basismentioning
confidence: 99%
See 1 more Smart Citation
“…An HLA association with HLA B8DR3 suggests an underlying genetic predisposition to autoimmunity [65] and these patients often have other autoimmune disorders, such as thyroid disease or diabetes. [64] These observations led to the first experimental studies implicating the immune system. It was shown that patients with LEMS responded clinically to plasma exchange, and daily injection of LEMS IgG antibodies into mice reproduced the principal neurophysiologic changes of LEMS.…”
Section: Immunological Basismentioning
confidence: 99%
“…[64] Typically, weakness improves during sustained effort as can be shown clinically or by electromyography. The compound muscle action potential is very small but increases during high-frequency stimulation or following a brief period of voluntary contraction.…”
Section: Vincent: Neuromuscular Autoimmunitymentioning
confidence: 99%
“…To define the clinical associations with AGNA, we studied the serum of 113 patients without PNS and SCLC, 122 with other cancer types, and 19 with idiopathic LEMS, defined by the absence of cancer after at least 3 years of follow-up (O'Neill et al, 1988). To ascertain the frequency of AGNA among different PNS associated with SCLC, we reviewed the presence of AGNA immunoreactivity in 30 patients with paraneoplastic LEMS, 27 with paraneoplastic cerebellar degeneration (PCD), 10 with sensory neuropathy, 10 with opsoclonus, and 8 with limbic encephalitis.…”
Section: Patientsmentioning
confidence: 99%
“…Autonomic dysfunctions, mostly xerostomia, occur in approximately 80% of the patients; other symptoms include impotence in men and loss of the libido in women 2,11 . Both patients in this report presented xerostomia and reduction of the libido.…”
Section: Discussionmentioning
confidence: 99%
“…Over 50% of the cases are related with oat cell lung carcinoma [1][2][3] . Lambert-Eaton syndrome has also been associated with squamous cell lung carcinoma, mixed tumors of the parotid glands, systemic mastocytosis, sarcomas, kidney carcinoma and other malignant neoplastic diseases [3][4][5] .…”
mentioning
confidence: 99%